Arginine Is a Critical Substrate for the Pathogenesis of Pseudomonas aeruginosa in Burn Wound Infections - Jake Everett (American Society for Microbiology, 2017)
ABSTRACT Environmental conditions affect bacterial behavior and can greatly influence the course of an infection. However, the environmental cues that elicit bacterial responses in specific infection sites are relatively unknown. Pseudomonas aeruginosa is ubiquitous in nature and typically innocuous. However, it is also one of the most prevalent causes of fatal sepsis in burn wound patients. The aim of this study was to determine the impact of environmental factors, specifically the availability of arginine, on the pathogenesis of P. aeruginosa in burn wound infections. Comparison of burned versus noninjured tissue revealed that l-arginine (l-Arg) was significantly depleted in burn wounds as a consequence of elevated arginase produced by myeloid-derived suppressor cells. We also observed that l-Arg was a potent chemoattractant for P. aeruginosa, and while low concentrations of l-Arg increased P. aeruginosa’s swimming motility, high concentrations resulted in diminished swimming. Based on these observations, we tested whether the administration of exogenous l-Arg into the burn wound could attenuate the virulence of P. aeruginosa in thermally injured mice. Administration of l-Arg resulted in decreased P. aeruginosa spread and sepsis and increased animal survival. Taken together, these data demonstrate that the availability of environmental arginine greatly influences the virulence of P. aeruginosa in vivo and may represent a promising phenotype-modulating tool for future therapeutic avenues. IMPORTANCE Despite our growing understanding of the pathophysiology of burn wounds and the evolution of techniques and practices to manage infections, sepsis remains a significant medical concern for burn patients. P. aeruginosa continues to be a leader among all causes of bacteremic infections due to its tendency to cause complications in immunocompromised patients and its ubiquitous presence in the hospital setting. With the unforgiving emergence of multidrug-resistant strains, it is critical that alternative strategies to control or prevent septic infections in burn patients be developed in parallel with novel antimicrobial agents. In this study, we observed that administration of l-Arg significantly reduced bacterial spread and sepsis in burned mice infected with P. aeruginosa. Given the safety of l-Arg in high doses and its potential wound-healing benefits, this conditionally essential amino acid may represent a useful tool to modulate bacterial behavior in vivo and prevent sepsis in burn patients.